2021
DOI: 10.1021/acs.organomet.0c00789
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Nickel-Catalyzed Regioselective Carboxylation of Allylic Alcohols

Abstract: The recently reported nickel-catalyzed direct carboxylation of allylic alcohol eliminates the necessity for preactivation of substrates in traditional strategies and generates linear β, γ-unsaturated carboxylic acids with high E/Z selectivity. Motivated by the significant experimental advantages and the mechanistic ambiguity (in the C−O activation mode of the allylic alcohol, the rate-and regio-/stereoselectivity-determining steps, etc.), we conducted a detailed study on the mechanism of Nicatalyzed carboxylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 79 publications
3
19
0
Order By: Relevance
“…To the best of our knowledge, there has been little research on the effect of ligated water to the nickel center . According to Fu’s calculation, the preactivation of alcohol to allylic hydrogen carbonate is essential in the presence of CO 2 and water . Water mainly functions as a proton transfer agent since direct reaction of allylic alcohol 1 with carbon dioxide is found to be difficult.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…To the best of our knowledge, there has been little research on the effect of ligated water to the nickel center . According to Fu’s calculation, the preactivation of alcohol to allylic hydrogen carbonate is essential in the presence of CO 2 and water . Water mainly functions as a proton transfer agent since direct reaction of allylic alcohol 1 with carbon dioxide is found to be difficult.…”
supporting
confidence: 90%
“…The outcome indicates that HEH may also function as the hydride donor in spite of water, albeit the D level (18%) was lower . Nevertheless, the reaction gave a trace amount of 2a when LiOAc was not added, manifesting that the ligand change of hydrogen carbonate with LiOAc is still necessary for a more stable intermediate. , …”
supporting
confidence: 67%
See 1 more Smart Citation
“…Mechanistic studies on Mei's Ni‐catalyzed regioselective carboxylation of allyl alcohols were carried out in 2021 by Yu, Fu, and co‐workers using DFT calculations [17] . They concluded that the contaminant H 2 O acted as a proton shuttle in the hydrogen‐shift process to enhance the activity of the allyl alcohol, and that this activation step is the rate‐determining step of the overall reaction.…”
Section: Thermally Promoted Reactionsmentioning
confidence: 99%
“…To overcome these problems, in situ activation strategies for allyl alcohols have been gradually developed, in which the electron-deficient species, including Lewis or Brønsted acids, are used to activate C–O bonds by forming hydrogen bonds or Lewis acid–base interaction with the hydroxyl groups of allyl alcohols, such as alkyl alcohols, phenol derivatives, alkyl carboxylic acids, benzoic acid derivatives, phosphonic acid, and some boron reagents (Scheme b). In this way, the transition metal catalyst is coordinated with the double bond of allyl alcohol ( INA ), and then, the activator is complexed with the hydroxyl group through the intermolecular interaction to form intermediate INB , which is then converted to the metal allyl zwitterion species INC via C–O bond cleavage for the subsequent transformation. , …”
Section: Introductionmentioning
confidence: 99%